Se, hvilket menneske! En undersøgelse af mennesket som etisk subjekt hos Dietrich Bonhoeffer med fokus på inspirationen fra Søren Kierkegaard - Plougmann , Agnes Marie; Nissen, Ulrik (Dansk Teologisk Tidsskrift, 2025)
The article seeks to shed new light on Dietrich Bonhoeffer’s Christian ethics by exploring the human being as an ethical agent in his work. Here, the inspiration from Søren Kierkegaard cannot be denied. However, the similarities between the two reach further than has hitherto been widely acknowledged. The emphasis on the individual in the earlier works of Bonhoeffer, such as Discipleship, does not fade away in his later works; the Kierkegaard-inspired faith and contemplation of the individual is the basis upon which Bonhoeffer’s Christian ethics stand. It must therefore be acknowledged that, for Bonhoeffer, the Christian human being does not find herself in a passive state regarding Christian ethical action, as has often been assumed. By exploring Bonhoeffer’s understanding of the individual and his inspiration from Kierkegaard, the works of both will be further illuminated and the Lutheran legacy that they share will be clarified.